Vital pulp therapy with two different calcium-silicate cements: two cases report - Shiva Alvandifar; Naeime Rayiat (Babol University of Medical Sciences, 2018)
It is a worthy aim to preserve the pulp vitality in teeth with immature root in order to continue the root's maturation. Traumatic injuries and caries are two main reasons for pulp exposure in immature teeth. This article describes two vital pulp therapies on two patients, a nine-year-old boy with traumatized central tooth and a 10-year-old boy with caries exposure in a premolar tooth. Both teeth had open apices in radiography. After removing inflamed pulp, the pulp cap was done using calcium silicate cements (CEM cement, MTA angelus) and then, the teeth were restored with filling material. In periodical follow-ups, both treated teeth remained functional, with complete root development and apex formation. Regarding to the potentiality of pulp healing in immature teeth, vital pulp therapy (VPT) can be an acceptable treatment. However, further clinical studies with longer follow-up periods are recommended.